2008
DOI: 10.1167/iovs.07-0762
|View full text |Cite
|
Sign up to set email alerts
|

Serial Measurements of Higher-Order Aberrations after Blinking in Patients with Dry Eye

Abstract: Increased HOAs in dry eye at least partially result from SPK above the optical zone. The low tear volume in dry eye may not cause sequential increases in HOAs after blinking. Sequential measurement of HOAs may be useful for evaluating the sequential changes in optical quality in patients with dry eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
112
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(124 citation statements)
references
References 33 publications
12
112
0
Order By: Relevance
“…This correlates with previous research computing corneal [2,3] and ocular [4] wavefront aberrations, and ocular MTF [14]. This also happens in dry-eye patients with a different dynamic pattern [5][6][7][8]. Tear film dynamics has an important impact on the higher-order aberrations of the anterior cornea [2,3] and hence on those of the whole eye [3].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This correlates with previous research computing corneal [2,3] and ocular [4] wavefront aberrations, and ocular MTF [14]. This also happens in dry-eye patients with a different dynamic pattern [5][6][7][8]. Tear film dynamics has an important impact on the higher-order aberrations of the anterior cornea [2,3] and hence on those of the whole eye [3].…”
Section: Discussionsupporting
confidence: 86%
“…Montés-Micó et al [7] have found differences in the dynamic of the tear film between normal and dry eyes, measuring the change in corneal aberrations after a blink. Ocular aberrations analysis, recently performed by Koh et al [4,8], also showed dynamic variability. These changes may be attributed to the increasingly irregular tear film [5].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…5 Tear film instability can lead to irregular astigmatism and increased higher-order aberrations, resulting in decreased visual functions. 2,6 Aging has been reported to result from deleterious damage to cells and tissues by free radicals. An imbalance between cell damage by free radicals and radical-scavenging antioxidant systems results in a condition that is called oxidative stress, which is associated with many age-related diseases and is also considered as a major factor in the process of senescence.…”
mentioning
confidence: 99%